MANAGEMENT DIRECTION IN THE FORMATION OF SOCIO-ECONOMIC POLICY OF UKRAINE - Vlasiuk, V. Ye. (Science and Transport Progress, 2008)
The paper is devoted to research of theoretic and methodic problems of forming the management influences to improve approaches of increasing the efficiency of economic model of management by the social-and-economic policy of Ukraine.